Low-Frequency Intravesical Electrical Stimulation for the Treatment of Acute Urinary Retention: A Promising Therapeutic Approach - Cao, Tingting; Xie, Bing; Yang, Siyuan; Wang, Jiaqi; Yang, Xiao; Shen, Boqiang; Lin, Xueke; Sun, Xiuli; Wang, Jianliu (Frontiers in Medicine, 2021)
Acute urinary retention (AUR) is a troublesome urological disease, which causes various lower urinary tract symptoms. However, only few studies explored and evaluated the effective treatments to improve AUR. We aimed to find an effective approach to cure AUR through comparing the efficacy of existing classical low-frequency transcutaneous electrical nerve stimulation (TENS) and novel intravesical electrical stimulation (IVES). A total of 24 AUR female rats were divided into 3 groups as follows: control, TENS, and IVES groups. Rats in the control group had no fake stimulation. Rats in the TENS and IVES groups underwent transcutaneous or intravesical stimulation of a symmetrical biphasic rectangular current pulse with a frequency of 35 Hz, 30 min per day, for seven consecutive days. IVES significantly reduced the actin expression in the submucosal layer but increased its expression in the detrusor layer (p = 0.035, p = 0.001). The neovascularization in the submucosal layer in the IVES group was significantly increased than in the other 2 groups (p = 0.006). Low-frequency IVES performed better than TENS in terms of simultaneously relieving bladder hyperactivity, accelerating epithelial recovery, and strengthening detrusor muscle. IVES may be a promising therapeutic approach for bladder dysfunction, specifically for AUR and overactive bladder in clinical practice.